Synthesis of Silica from Rice Husk Waste Using NaOH as a Reagent - Maipha Deapati Arief; Hermin Hardyanti Utami; Rismul Trianto Salawali; Awal Fajar Ramadhan; Hasmarini, Hasmarini; Windi, Windi (Innovative: Journal Of Social Science Research, 2025)
In this study, silica was synthesized from rice husk waste using NaOH as a reagent. Rice husk waste was selected as the silica source due to its abundant availability and high silica content. The synthesis method involved silica extraction with an alkaline solution followed by precipitation using various types of acids to obtain optimal silica. The extraction process was conducted with two time variations: 60 minutes and 90 minutes. The physicochemical characteristics analyzed included moisture content, humidity, and adsorption capacity. The results indicated that silica extracted with a 90-minute variation was more optimal, as evidenced by a humidity level of 48% and a moisture content of 0.14%.